PECULIARITIES OF THE COURSE OF PEROXIDE OXIDATION PROCESSES IN GILTS DEPENDING ON THEIR PHYSIOLOGICAL STATE - Usenko, S. O.; Shostya, A. M.; Slynko, V. G.; Bondarenko, O. M.; Bereznytskyi, V. I.; Shaferivskyi, B. S.; Chukhlib, Ye. V. (Scientific Progress & Innovations, 2019)
Experimental data presented by many scientists indicate at the leading importance of peroxide oxidation processes in providing mobility, sperm survival, oocyte maturation, and impregnation. Being pregnant, the organism of gilts is under the impact of oxidative stress, which may be accompanied by violating the processes of placenta, fetal development, and premature delivery. This requires the development of antioxidant nutrition programs based on a deep understanding of the mechanism of their specific effect. The purpose of the research was to determine the peculiarities of the processes of peroxidation oxidation in gilts depending on their physiological state. 5 clinically healthy pigs of the Ukrainian Steppe White breed 8 months of age and the body weight of 125– 130 kg were used in experiments based on the principle of analogues. Blood samples were taken at different stages of the reproductive cycle: luteal phase, estrus, on the 15th, 20th, 30th, 60th, 90th, 104th, 113th days of pregnancy and in 12 hours after farrowing. The intensity of the processes of peroxidation in the blood was studied by the activity of xanthine oxidase, the concentration of diene conjugates, and the content of TBAreactive compounds. The level of antioxidant protection was evaluated by the activity of superoxide dismutase, catalase activity, the content of reduced glutathione, ascorbic and dehydroascorbic acids, vitamins A and E. It was established that during estrus period the processes of peroxide oxidation in blood accelerated: the activity of xanthine oxidase grew, the content of diene conjugates increased by 1.6 times and the TBA- reactive compounds – by 1.9 times (p <0.05). These changes were accompanied by decreasing the erythrocytes resistance to peroxide hemolysis by 64 % and increasing the level of antioxidant protection - the activity of superoxide dismutase, the amount of vitamins A (p <0.05) and E. It was established that before farrowing, there was peroxidation intensification in gilts because of increasing the activity of xanthine oxidase, superoxide dismutase, and reducing catalase. These changes took place on the background of accelerating the process of peroxide oxidation – increasing the concentration of diene conjugates (p <0.05), TBA-reactive compounds (p <0.01), and decreasing the amount of low molecular weight antioxidants: reduced glutathione, vitamins A and E (p <0.01). The peculiarities of the course of peroxide oxidation processes in the gilts’ blood are determined by the periods of sexual cycle and pregnancy.